Foucault on Laughter: Фуко за смеењето - Ivanchikova, Alla (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Alla Ivanchikova | Ала Иванчикова Title (English): Foucault on Laughter Title (Macedonian): Фуко за смеењето Translated by (English to Macedonian): no record Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 50-64 Page Count: 14 Citation (English): Alla Ivanchikova, “Foucault on Laughter,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 50-64. Citation (Macedonian): Ала Иванчикова, „Фуко за смеењето“, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 50-64.